Pengaruh Kompres Hangat Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif Di RSUD Dr.Tengku Mansyur Kota Tanjung Balai Tahun 2023 - Maysarah Nasution; Kamelia Sinaga; Azri Yani; Ribur Sinaga; Imran Saputra Surbakti (NAJ : Nursing Applied Journal, 2023)
The scope of implementation of lactation management starts from the pregnancy period, after delivery, and the baby's breastfeeding period. Lactation is the entire breastfeeding process starting from the production of breast milk to the process of the baby sucking and swallowing the breast milk. Babies who are exclusively breastfed have good perinatal growth and reduce obesity. Breastfeeding a baby on demand can increase levels of the hormone oxytocin in a mother's body postpartum and avoid the risk of swelling or dams/blockages in the nipple ducts during the lactation period (Sutanto, 2018). This research aims to analyze the relationship between postpartum mothers' knowledge about breast care and the smooth production of breast milk in Hospital Tengku Mansyur tanjung balai city Regency in 2023. This research is correlational with a cross sectional approach and bivariate data analysis is data analysis used in research to determine the relationship or influence of variables independent (independent) with a dependent (dependent) variable using Chi Square analysis with a significant p-value (0.05) (Hardani, 2020) Based on the research results. Based on the results of statistical tests using Chi-Square, it was obtained with a p value of 0.001 that there was a relationship between the knowledge of postpartum mothers regarding breast care and the smooth production of breast milk in Hospital Tengku Mansyur tanjung balai city Regency in 2023.This means that there is a relationship between the knowledge of postpartum mothers about breast care and the smooth production of breast milk in Hospital Tengku Mansyur tanjung balai city Regency in 2023